THE EFFECT OF PAPAYA (Carica papaya L.) SEED EXTRACT THROUGH DRINKING WATER ON THE PERCENTAGE OF COMERCIAL CUTTING OF BROILER CHICKEN - I G. A. A. M., Dwipayana; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
This study aims to determine the effect of giving papaya seed extract (Carica papaya L.) through drinking water on the percentage of commercial broiler carcass pieces. This research was conducted in Selanbawak Village, Marga District, Tabanan Regency, Bali which was carried out for 6 weeks. The design used was a completely randomized design with 4 treatments and 4 replications each containing 5 broilers so that the total number of broilers used was 80. The treatments given were broiler chickens given drinking water without papaya seed extract (A), 1% papaya seed extract (B), 2% papaya seed extract (C), 3% papaya seed extract (D). The variables observed were the percentage of carcass, chest, upper thigh, lower thigh, wing, and back. The results showed that the treatment of giving papaya seed extract levels of 1% (B), 2% (C) and 3% (D) through drinking water had no significant effect (P>0.05) from treatment A (without papaya seed extract) on chest percentage, upper thigh percentage, lower thigh percentage, wing percentage, back percentage. From this study it can be concluded that the administration of papaya seed extract (Carica papaya L.) through drinking water at a level of 1% - 3% has not had an effect on the percentage of broiler chicken carcass pieces   Key Word : Broiler chicken, papaya seed extract, commercial carcass